Williams expansion-based approximation of the stress field in an Al 2024 body with a crack from optical measurements (Fracture and Structural Integrity, 2017)
A study on the approximation of the stress field in the vicinity of crack tip in a compact tension specimen made from Al 2024-T351 is presented. Crack tip stress tensor components are expressed using the linear elastic fracture mechanics (LEFM) theory in this work, more precisely via its multi-parameter formulation, i.e. by Williams power series (WPS). Determination of coefficients of terms of this series is performed using a least squares-based regression technique known as over deterministic method (ODM) for which displacements data obtained experimentally via optical measurements are taken as inputs. The stress fields reconstructed based on the displacement data obtained experimentally by means of optical measurements are verified by means of the stress field approximations derived for the normalized CT specimen via hybrid elements.
Keywords: Crack tip fields; Optical measurements; DIC; Williams power series; Higher-order terms; Stress field reconstruction; Multi-parameter approximation